2020
DOI: 10.21203/rs.3.rs-96096/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessing information-sharing networks within small-scale fisheries and the implications for conservation interventions

Abstract: The effectiveness of biodiversity conservation interventions is often dependent on local resource users' underlying social interactions. However, it remains unclear how fine-scale differences in information shared between resource users can influence network structure and the success of behavior-change interventions. Using network null models that incorporate a pre-network data permutation procedure, we compare information-sharing networks in a Peruvian fishing community where a trial conservation intervention… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…This nding indicates that the usual mechanisms that drive information sharing between gillnet skippers in the other shing-related networks (and potentially social networks generally) are not at play in the sea turtle bycatch information-sharing network [40,41]. The lack of discussion about sea turtle bycatch between gillnet skippers with similar levels of bycatch may potentially occur if some gillnet skippers with higher rates of sea turtle bycatch do not realise or appreciate that they have higher bycatch than other gillnet skippers in the community [44]. Indeed, previous research and eld observations from the study site have suggested that shers with higher bycatch rates tend not to put much effort into actively avoiding sea turtles captures unless they are speci cally incentivised to do so (i.e., through the local not-for-pro t's trial bycatch reduction initiative) [33].…”
Section: Structural Differences Between Information-sharing Networkmentioning
confidence: 99%
“…This nding indicates that the usual mechanisms that drive information sharing between gillnet skippers in the other shing-related networks (and potentially social networks generally) are not at play in the sea turtle bycatch information-sharing network [40,41]. The lack of discussion about sea turtle bycatch between gillnet skippers with similar levels of bycatch may potentially occur if some gillnet skippers with higher rates of sea turtle bycatch do not realise or appreciate that they have higher bycatch than other gillnet skippers in the community [44]. Indeed, previous research and eld observations from the study site have suggested that shers with higher bycatch rates tend not to put much effort into actively avoiding sea turtles captures unless they are speci cally incentivised to do so (i.e., through the local not-for-pro t's trial bycatch reduction initiative) [33].…”
Section: Structural Differences Between Information-sharing Networkmentioning
confidence: 99%